Drug effects on metabolic profiles of Schistosoma mansoni adult male parasites detected by 1H-NMR spectroscopy. - Alessandra Guidi; Greta Petrella; Valentina Fustaino; Fulvio Saccoccia; Sara Lentini; Roberto Gimmelli; Giulia Di Pietro; Alberto Bresciani; Daniel Oscar Cicero; Giovina Ruberti (Public Library of Science (PLoS), 2020)
Schistosomiasis is one of the most devastating neglected tropical parasitic diseases caused by trematodes of the genus Schistosoma. Praziquantel (PZQ) is today the only drug used in humans and animals for the treatment of schistosomiasis but unfortunately it is poorly effective on larval and juvenile stages of the parasite. Therefore, it is urgent the discovery of new drug targets and compounds. We have recently showed that the anti-anginal drug perhexiline maleate (PHX) is very active on multiple developmental stages of Schistosoma mansoni in vitro. It is well known that PHX impacts the lipid metabolism in mammals, but the final target on schistosomes still remains unknown. The aim of this study was to evaluate the ability of 1H nuclear magnetic resonance (NMR) spectroscopy in revealing metabolic perturbations due to PHX treatment of S. mansoni adult male worms. The effects of PHX were compared with the ones induced by vehicle and gambogic acid, in order to detect different metabolic profiles and specificity of the PHX action. Remarkably a list of metabolites associated to PHX-treatment was identified with enrichment in several connected metabolic pathways including also the Kennedy pathway mediating the glycerophospholipid metabolism. Our study represents the first 1H-NMR metabolomic approach to characterize the response of S. mansoni to drug treatment. The obtained "metabolic fingerprint" associated to PHX treatment could represent a strategy for displaying cellular metabolic changes for any given drug and to compare compounds targeting similar or distinct biochemical pathways.